Effects of personal control for thermal comfort in long-distance trains - Maier, Julia; Zierke, Oliver; Hoermann, Hans-Juergen; Goerke, Panja (Energy and buildings, 2021)
[Display omitted] •Effects of thermo-specific self-efficacy for climate comfort in trains were analysed.•Thermal comfort ratings had significant relationships with climate satisfaction.•Thermo-specific self-efficacy contributed substantially to the prediction of climate satisfaction.•Thermo-specific self-efficacy moderated effects of exercised control on climate satisfaction. As a result of its low environmental impact the railway system is the prime candidate to enable domestic and continental mass passenger mobility. One important aspect determining the attractiveness of rail journeys is the thermal comfort that is provided in a passenger rail car. Newer approaches focusing on the improvement of thermal comfort in passenger rail cars are based on the idea to employ personalized comfort zones. It is generally assumed that individual control over indoor climate settings contributes to the passengers’ thermal comfort. The studies presented here further examine this assumption by considering the concept “thermo-specific self-efficacy” (specSE) as psychological construct in the context of thermal comfort in a railway car. Two studies with 11 human subject test runs including 172 subjects in total were performed in a mock-up of a passenger rail car. Environmental climate conditions in the mock-up were controlled and measured. It was found that specSE can be considered as a distinct construct and that it contributed substantially to the prediction of thermal comfort and climate satisfaction. In addition, it moderated the effects of available and exercised control. The presented results expand upon earlier findings for the concept of personal control and confirm the role of specSE for thermal comfort predictions.